New Myxophagan water beetles from Madagascar (Coleoptera: Torridincolidae, Hydroscaphidae) - Perkins, Philip D.; Bergsten, Johannes (Zootaxa, 2019)
Myxophagan water beetles from Madagascar are comprehensively revised. Holotypes of the two previously known species are re-described and illustrated. Six new species of Incoltorrida Steffan and one new species of Hydroscapha LeConte are described and illustrated. The larvae of Incoltorrida quintacostata are illustrated and discussed. The presence of peritrich ciliates of the genus Platycola Kent on specimens of Incoltorrida madagassica Steffan is discussed and illustrated. Habitus, habitats, and male genitalia are illustrated, and distributions are mapped. The following new species are described (type localities parenthetic): Incoltorrida benesculpta n. sp. (Fianarantsoa, 3.2km S Ambohimanjaka); I. galoko n. sp. (Antsiranana, Diana, Ambilobe, Antsaba, Galoko mountains ); I. magna n. sp. (Antsiranana, Diana, Ambilobe, Antsaba, Galoko mountains); I. marojejy n. sp. (Antsiranana, Sava, Marojejy National Park); I. quintacostata n. sp. (Fianarantsoa, 3.5km N Ivato); I. zahamena n. sp. (Toamasina, Alaotra-Mangoro, Zahamena National Park); Hydroscapha andringitra n. sp. (Fianarantsoa, Ambilavao, Sendrisoa, approx. 10km N of Andringitra National Park).